Magnetohydrodynamics effect of Marangoni nano boundary layer flow and heat transfer with CNT and radiation - Sneha K.N.; Bognar G.; Mahabaleshwar U.S.; Singh D.K.; Singh O.P. (My University, 2025)
The investigation focuses on 2-dimensional MHD steady incompressible flow and heat transfer. To improve the thermal efficiency, nanoparticles are added to the water base fluid and a strong transverse magnetic field is applied. After performing the appropriate similarity transformations, the governing equations for the prescribed flow form a system of PDEs, which are then converted to a system of ODEs. After solving the resulting system analytically, the velocity profile and temperature distribution are expressed in terms of exponential and Gamma functions. The existence of physical threats and the flow field are influenced by factors such as magnetic field, viscoelasticity, and suction/injection. However, the temperature field is influenced by factors including thermal radiation, Prandtl number, and others. The result shows that the axial velocity is influenced by the viscoelastic constraint, magnetic field, and suction/injection parameters. Graphical representations of the effects of mass transpiration on velocity profiles and temperature distribution are provided. It was discovered that Marangoni convection improved the rate of heat transfer. In contrast, it decreases as a result of the applied magnetic energy. Additionally, SWCNT nano liquid is hotter than nano liquid. Numerous commercial and scientific applications of the issue under discussion can be found in fields like aviation and medicine. Under the influence of radiation, the effects of MHD and suction/injection on the fluid's flow and heat transfer properties are investigated. The results of each profile's solution and the results of the interface velocity and rate of surface heat transfer are shown in the form of figures. © 2023